Affective Benefits of Study Abroad for Second Language Learners (Comparative & International Education Series, 2021)
Research on the effects of study abroad (SA) on second language (L2) learners has been largely geared towards measuring linguistic gains through such overseas experiences. This chapter aims to address the issue of the effects of SA experience from a different perspective, by focusing on the affective benefits for L2 learners, which have recently started to receive attention from the research community. In this chapter, I first review previous studies that have examined the changes in L2 learners’ anxiety, willingness to communicate in the target language, and L2 motivation through SA experience. I then discuss the methodological issues related to SA research on affective benefits for L2 learners, focusing on research design, participant profiles, and target SA programs. The chapter also provides implications for future SA research on affective variables.